Association between driving pressure-guided ventilation and postoperative pulmonary complications in surgical patients: a meta-analysis with trial sequential analysis - Gu, Wan-Jie; Cen, Yun; Zhao, Feng-Zhi; Wang, Hua-Jun; Yin, Hai-Yan; Zheng, Xiao-Fei (British journal of anaesthesia : BJA, 2024)
Prior studies have reported inconsistent results regarding the association between driving pressure-guided ventilation and postoperative pulmonary complications (PPCs). We aimed to investigate whether driving pressure-guided ventilation is associated with a lower risk of PPCs. We systematically searched electronic databases for RCTs comparing driving pressure-guided ventilation with conventional protective ventilation in adult surgical patients. The primary outcome was a composite of PPCs. Secondary outcomes were pneumonia, atelectasis, and acute respiratory distress syndrome (ARDS). Meta-analysis and subgroup analysis were conducted to calculate risk ratios (RRs) with 95% confidence intervals (CI). Trial sequential analysis (TSA) was used to assess the conclusiveness of evidence. Thirteen RCTs with 3401 subjects were included. Driving pressure-guided ventilation was associated with a lower risk of PPCs (RR 0.70, 95% CI 0.56–0.87, P=0.001), as indicated by TSA. Subgroup analysis (P for interaction=0.04) found that the association was observed in non-cardiothoracic surgery (nine RCTs, 1038 subjects, RR 0.61, 95% CI 0.48–0.77, P< 0.0001), with TSA suggesting sufficient evidence and conclusive result; however, it did not reach significance in cardiothoracic surgery (four RCTs, 2363 subjects, RR 0.86, 95% CI 0.67–1.10, P=0.23), with TSA indicating insufficient evidence and inconclusive result. Similarly, a lower risk of pneumonia was found in non-cardiothoracic surgery but not in cardiothoracic surgery (P for interaction=0.046). No significant differences were found in atelectasis and ARDS between the two ventilation strategies. Driving pressure-guided ventilation was associated with a lower risk of postoperative pulmonary complications in non-cardiothoracic surgery but not in cardiothoracic surgery. INPLASY 202410068.